Endothelial Nitric oxide synthase gene polymorphism and coronary arrtery disease in Asian populations - Ibrahim, Wisam Nabeel; Sabria, Muhammed Azali; Muhammad Musa, Nurul Ashikin; Nik Ahmad, Nik Nur Fatnoon; Abdullah, Nor Zamzila; A. Talib, Norlelawati (Asian Network for Scientific Information, 2017)
Background and Objectives: Glu298Asp endothelial Nitric Oxide Synthase (eNOS) gene polymorphism results in a reduced bioavailability of Nitric Oxide (NO) & prones to atherosclerosis. Even though there were more than 15 studies conducted on Asian populations investigating the role of this polymorphism in coronary artery disease (CAD), however; the representative data from Malaysia is still not clear. The aim of this study was to assess the association between Glu298Asp polymorphism and CAD through original research with the integration of other studies through meta-analysis approach. Methods: The study included 185 CAD patients and 188 control participants. Polymerase chain reaction – restriction fragment length polymorphism (PCR-RFLP) assay was used to identify the genotype of the study participants. The results were confirmed by nucleotide sequencing of selected genotypes, and the association with CAD was tested using SPSS version 19 with Chi-square test. Execution of meta-analysis involved 23 Asian case-control studies using Revman meta-analysis software version 5.3. Results: The study has demonstrated a significant association between Glu298Asp genotype variants and CAD patients (p < 0.001). Asp allele was a significant predictor for CAD ([p=0.001, OR=2.186 (1.53-3.125; CI= 95 %)]. Through meta-analysis the combined cohort data showed significant Glu298Asp risk to CAD [p<0.0001, OR=2.41 (1.61-3.59); Heterogeneity test (I2=10%, p=0.33)]. Conclusion: Homozygous Asp genotype of Glu298Asp polymorphism potentiates a risk for CAD.